2017
DOI: 10.3389/fped.2017.00121
|View full text |Cite
|
Sign up to set email alerts
|

Myalgic Encephalomyelitis/Chronic Fatigue Syndrome Diagnosis and Management in Young People: A Primer

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a complex disease that affects children and adolescents as well as adults. The etiology has not been established. While many pediatricians and other health-care providers are aware of ME/CFS, they often lack essential knowledge that is necessary for diagnosis and treatment. Many young patients experience symptoms for years before receiving a diagnosis. This primer, written by the International Writing Group for Pediatric ME/CFS, provides informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
292
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(318 citation statements)
references
References 184 publications
(241 reference statements)
16
292
0
10
Order By: Relevance
“…13 In addition, chronic illness occurring at a time of significant changes in young people, disrupting their educational, social and physical activities, creates significant challenges both for the young people and their families. 14,15 It is the commonest cause of reduced time at school 16,17 and has a significant impact on educational functioning. 18 Although there are other chronic illnesses during childhood that have physical, emotional, cognitive and educational impacts, [19][20][21][22]24 this illness does affect all these areas.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…13 In addition, chronic illness occurring at a time of significant changes in young people, disrupting their educational, social and physical activities, creates significant challenges both for the young people and their families. 14,15 It is the commonest cause of reduced time at school 16,17 and has a significant impact on educational functioning. 18 Although there are other chronic illnesses during childhood that have physical, emotional, cognitive and educational impacts, [19][20][21][22]24 this illness does affect all these areas.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The majority of patients with CFS report that it took longer than a year to receive a diagnosis, often because the condition is regarded as a diagnosis of exhaustive exclusion rather than a positive recognition of the characteristic fatigue state (Box 1). Necessary investigations include full blood count, urea, electrolyte and creatinine levels, liver and thyroid function tests, C‐reactive protein levels or erythrocyte sedimentation rate, and fasting blood glucose tests . Reassuringly, a systematic review of 26 studies examining CFS diagnosis in patients attending primary care with tiredness revealed a low prevalence of underlying medical conditions, including anaemia (2.8%), malignancy (0.6%), and other serious physical illnesses (4.3%) .…”
Section: Diagnosing Cfsmentioning
confidence: 99%
“…We retrieved publications from MEDLINE, PsycINFO, EMBASE, Cochrane and PubMed databases from 1988 to 2019 to consider aspects of clinical decision making in the diagnosis, assessment of prognosis, and management of CFS; provide an update on understanding of CFS pathophysiology; and identify priorities for improved care of patients with CFS and for future research. This review focuses on adult populations, but the condition also affects children and adolescents (reviewed elsewhere) …”
mentioning
confidence: 99%
“…Le syndrome de fatigue chronique (SFC) ou encéphalomyélite myalgique est une pathologie rare de l'adolescent et de l'adulte jeune caractérisée par une fatigue importante avec sensation d'épuisement, persistante depuis plus de 6 mois, sans autre cause identifiée et qui est associée à la présence d'au moins 4 critères mineurs sur 6 [86]. Elle est 3 à 4 fois plus fréquente dans le sexe féminin.…”
Section: Igg Anti-aliments Et Autres Pathologiesunclassified